Tingkat Prestasi Belajar Matematika Ditinjau Dari Minat Dan Penggunaan Media IT Kelas VII Semester Genap Di Smp Muhammadiyah 1 Surakarta Tahun 2015/2016 - Aini, Khusnul Muslimah; , Prof. Dr. Sutama, M.Pd (2016)
The learning achievement is the result obtained as a result of the activities students in learning. Interest and IT media role in the level of student achievement. The purpose of this study: (1) Examine differences in learning achievement level in terms of interest in learning, (2) Examine the differences in the level of learning achievement in terms of the use of IT media, (3) Examine interactions between interest and media use of IT to the level of learning achievement. This research is a quantitative comparison. The population is all students of class VII second semester SMP Muhammadiyah 1 Surakarta academic year 2015/2016. The sampling technique using propotional random sampling. Data were collected by observation, questionnaire, and documentation. Data analysis techniques: analysis of variance of two different cell. The results of data analysis using a significance level of 5% was obtained: (1) There are differences in the level of mathematics achievement among students in terms of the interests of low, medium, and high, with FA = 6,5927, (2) There were no differences in levels of mathematics achievement in terms of media usage of IT by category never, sometimes, often, with FB = 2,1685, (3) There is no interaction between interest and media use of IT to the level of mathematics achievement, with FAB = 0,1015.